STRATEGI MARKETING POLITIK PADA CALEG MILENIAL DI KABUPATEN BUTON SELATAN - Nabila Salam (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
The purpose of this study was to determine the political marketing strategy of the millennial generation in South Buton Regency. This research uses a qualitative descriptive method. The informants of this research came from 2 members of the millennial generation Regional House of Representatives in South Buton Regency. The data collection techniques used were observation, in-depth interviews, and documentation studies. Researchers used source triangulation techniques to test the validity of data related to the research problem under study. The results of this study show that the two informants have different approaches to political marketing strategies, which are reflected in the use of Segmentation, Targeting, and Positioning that are tailored to the characteristics of the community and the region. DH highlights himself as an adaptive figure, understands specific needs, and respects local cultural traditions. On the other hand, KS builds an image as someone who is deep in cultural understanding, collaboration-oriented, and able to combine traditional and modern approaches. Both legislative candidates try to position themselves as leaders who can meet the needs of the people in their region and work together to achieve common interests.